Targeting the KLF5/PI3K/AKT axis as a therapeutic strategy to overcome neoadjuvant chemoresistance in colorectal cancer - Gao, Meiling; Qian, Jiahao; Xia, Ping; Liu, Wancheng; Jiang, Yunjia; Xia, Yuchang; Yao, Xin; Jiao, Qingqing; Wei, Minggang (Frontiers in Immunology, 2025)
BackgroundOxaliplatin-based neoadjuvant chemotherapy (NAC) is the standard treatment for advanced colorectal cancer (CRC), yet resistance to NAC poses a significant clinical challenge.MethodsTo investigate the mechanisms of chemoresistance, we analyzed single-cell RNA sequencing (scRNA-seq) data from CRC patients undergoing NAC. Comprehensive analyses, including InferCNV, differentially expressed genes analysis, pathway enrichment, cell communication, and SCENIC were performed. High-throughput drug screening identified potential therapeutic candidates targeting chemoresistance pathways, and the efficacy of targeting the KLF5/PI3K/AKT axis in combination with oxaliplatin was explored in animal models.ResultsNAC effectively reduced tumor burden and enhanced T_NK cell infiltration in responsive tumors. Notably, NAC-resistant cell clusters exhibited activation of fatty acid-related metabolic pathways and demonstrated limited immune infiltration. Transcriptional analysis identified KLF5 as a potential driver of chemotherapy resistance. Based on these findings, we developed a KLF5 regulon-associated risk score model with significant potential for predicting CRC patient prognosis. Mechanistically, KLF5 activation of the PI3K/AKT pathway conferred chemoresistance in CRC cells. Through high-throughput screening, GDC-0941, a PI3K/AKT inhibitor, emerged as a promising therapeutic agent that synergistically enhanced oxaliplatin efficacy and overcame resistance in preclinical models.ConclusionsTargeting the KLF5/PI3K/AKT axis may enhance chemotherapy efficacy and overcome drug resistance in CRC.